2021
DOI: 10.1021/acscatal.1c01998
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Investigation of Charge Performance in Anatase TiO2 Powder for Methane Conversion by Vis–NIR Spectroscopy

Abstract: The intrinsic behavior of photogenerated charges and reactions with chemicals are key for a photocatalytic process. To observe these basic steps is of great importance. Here we present a reliable and robust system to monitor these basic steps in powder photocatalysts, and more importantly to elucidate the key issue in photocatalytic methane conversion over the benchmark catalyst TiO 2 . Under constant excitation, the absorption signal across the NIR region was demonstrated to be dominate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…This case of study demonstrated that TRIR is capable of systematically characterizing midgap energy levels in semiconductor photocatalysts. In addition, the near IR spectroscopy can also provide complementary information to TRIR, 103 in which we found that the free or shallow trapped photoelectrons in TiO 2 could be monitored readily using near IR spectroscopies.…”
Section: Trir Studies On Intrinsic Photocatalystsmentioning
confidence: 94%
“…This case of study demonstrated that TRIR is capable of systematically characterizing midgap energy levels in semiconductor photocatalysts. In addition, the near IR spectroscopy can also provide complementary information to TRIR, 103 in which we found that the free or shallow trapped photoelectrons in TiO 2 could be monitored readily using near IR spectroscopies.…”
Section: Trir Studies On Intrinsic Photocatalystsmentioning
confidence: 94%
“…Most recently, we constructed an in situ vis–NIR spectroscopy system to elucidate the initial steps of methane photoactivation over anatase TiO 2 ( Figure 8 a). 52 From the in situ experimental study, under constant light irradiation, the intensity of photogenerated electrons on anatase TiO 2 increased in the NIR region under methane atmosphere as compared to that under argon gas. Combined with the significantly decreased signal intensity of electrons under air condition ( Figure 8 b), it was strongly evidenced that methane was a hole scavenger in photocatalytic methane conversion ( Figure 8 c).…”
Section: Strategies To Enhance Photocatalytic Efficiencymentioning
confidence: 99%
“…Further experimental and DFT results demonstrated the inverse correlation between the yield of deep-trapped long-live inactive electrons over g-C 3 N 4 and the related H 2 production. Most recently, we constructed an in situ vis–NIR spectroscopy system to elucidate the initial steps of methane photoactivation over anatase TiO 2 (Figure a) . From the in situ experimental study, under constant light irradiation, the intensity of photogenerated electrons on anatase TiO 2 increased in the NIR region under methane atmosphere as compared to that under argon gas.…”
Section: Strategies To Enhance Photocatalytic Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…As the oxygen source for CH 3 OH came from both H 2 O and O 2 , it was accordingly concluded that •CH 3 radicals reacted with both •OH radicals and •OOH radicals (Equation 6 and 7), which were generated from H 2 O oxidation and O 2 www.advancedsciencenews.com www.solar-rrl.com reduction, respectively. The generation of HCHO [30] was derived from further oxidation of the as-produced CH 3 OOH and CH 3 OH. [7] The overoxidation of C1 oxygenates to CO 2 might be caused by •OH radicals.…”
Section: Mechanism Investigationmentioning
confidence: 99%